Community matters: Heterogenous impacts of a sanitation intervention - Laura Abramovsky; Britta Augsburg; Melanie Lührmann; Francisco Oteiza; Juan Pablo Rud (Institute for Fiscal Studies (IFS), 2019)
We study the effectiveness of a community-level information intervention aimed at reducing open defecation (OD) and increasing sanitation investments in Nigeria. The results of a cluster-randomized control trial conducted in 247 communities between 2014 and 2018 suggest that average impacts are exiguous. However, these results hide important community heterogeneity, as the intervention has strong and lasting effects on OD habits in poorer communities. This result is robust across several measures of community socio-economic characteristics, and is not driven by baseline differences in toilet coverage. In poor communities, OD rates decreased by 9pp from a baseline level of 75%, while we find no effect in richer communities. The reduction in OD is achieved mainly through increased toilet ownership (+8pp from a baseline level of 24%). Finally, we combine our study with data from five other trials of similar interventions to show that estimated impacts are stronger in poorer contexts, rationalizing the wide range of estimates in the literature and providing plausible external validity, with implications for program scale-up. Our findings point to community wealth as a widely available key statistic for effective intervention targeting.
Keywords: 330; External validity; Heterogeneous Treatment Effects; Sanitation; Information; Cluster-Randomized Control Trial